SERUM LEVEL OF IgG AND WORM LOAD IN MALE SWISS ALBINO MICE INOCULATED WITH L3 LARVAE OF ANCYLOSTOMA CANINUM - V. VIVEKA VARDHANI,; G. SAKUNTHALA, (The Bioscan, 2012)
Experiments were conducted to study the level of serum IgG and the effect of infective, filariform larvae of Ancylostoma caninum in male swiss albino mice (6 to 8 wks old, 23-26 g wt). Three groups of mice (group A, 500 doses; group B, 1000 dose; group C, 2000 dose) were infected orally with a single dose of infected larvae. The decrease of serum IgG level in all the experimental groups of mice was influenced by the retained worm load in the host system. No correlation was found between the level of serum IgG and retained worm burden in the host system.